Learning about Partographs for Fifth Semester Students of STIKes Salsabila - siswosuharjo, partono; Fathiyati, Fathiyati (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Maternal mortality is still very high every year. One way to reduce the death rate is to increase the knowledge of health workers, in an effort to detect early labor, namely by using a partograph. Remembering that the function of the partograph is to record the results of observations and progress of labor and detect whether the labor process is progressing normally. In this way, early detection can also be carried out for any possibility of prolonged labor. The aim of this research is to provide learning about partographs to students in Semester V of STIKes Salsabila based on their ability to source information, length of study, experience in filling out partographs when assisting with childbirth, applying partographs, and experience in practice. This research is a simple descriptive study, using a sample of 92 fifth semester female students as research objects. The results of the research can be concluded that learning about partography for Semester V female students can be categorized as good. The researcher's advice to female students is to maintain and improve their abilities regarding partography